1968
DOI: 10.1115/1.3597486
|View full text |Cite
|
Sign up to set email alerts
|

Pool Boiling on Polished and Chemically Etched Stainless-Steel Surfaces

Abstract: This paper presents pool boiling data at atmospheric pressure for mechanically polished and chemically etched 304 stainless-steel surfaces in contact with distilled water. The surfaces were prepared by these techniques to produce variation in nucleation sites. Surface roughness was varied from 2–61 rms. The results show the changes in heat transfer with varying rms surface roughness and preparation technique. The Rohsenow pool boiling correlation was used to discuss the data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…It is clearly demonstrated that the boiling curve shifts to the left as R a increases, which indicates better nucleate boiling heat transfer performance with increasing R a . This is consistent with previous studies that dealt with the effect of surface roughness on nucleate boiling heat transfer [4,6,25]. However, the change in CHF with increasing R a in Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It is clearly demonstrated that the boiling curve shifts to the left as R a increases, which indicates better nucleate boiling heat transfer performance with increasing R a . This is consistent with previous studies that dealt with the effect of surface roughness on nucleate boiling heat transfer [4,6,25]. However, the change in CHF with increasing R a in Fig.…”
Section: Resultssupporting
confidence: 93%
“…Using rigorous experiments, Rohsenow [2] included the surface effects in his boiling correlation by matching the surfacefluid combination to the proper coefficient, C sf . Subsequently, many studies have revealed the relationship between roughened surfaces and an increase in the number of nucleation sites, resulting in augmented boiling heat transfer [3][4][5][6]. Recent research efforts are focused on boiling heat transfer with a more complex surface exhibiting multiscale roughness [7], surface roughness accompanying a wettability change [8], and roughness in complex geometries [9].…”
Section: Introductionmentioning
confidence: 98%
“…Some studies in the literature have shown that roughening the surfaces only improved the boiling performance up to a certain point, after which additional roughening adds no benefit. [58][59][60] For surfaces produced using conventional manufacturing techniques, several researchers have noted the inability of commonly used surface roughness parameters, such as the RMS roughness or average roughness, to explain the variation in observed nucleate boiling heat transfer characteristics. 61,62 Also, numerous investigators have reported on the inefficacy of correlating nucleate boiling data using surface roughness parameters.…”
Section: Effect Of Surface Roughnessmentioning
confidence: 99%
“…Some of the earlier work includes those by Rohsenow [1], Hsu and Schmidt [2], Mostinski [3], Marto and Rohsenow [4], and Vachon et al [5]. Cooper [6] quantitatively assessed the effect of surface roughness on pool boiling correlation.…”
Section: Introductionmentioning
confidence: 99%